2023
DOI: 10.1002/app.53904
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional starch/carbon nanotube composites with segregated structure: Electrical conductivity, electromagnetic interference shielding effectiveness, thermal conductivity, and electro‐thermal conversion

Abstract: Conductive polymer composites with segregated structure (s‐CPCs) are widely used in the electronics industry. Achieving selective distribution of the conductive fillers in the polymer matrix is an effective way to construct s‐CPCs. In this work, the starch was used as the matrix and the carbon nanotube (CNT) was used as the conductive fillers to fabricate multifunctional s‐CPCs, via simple mechanical mixing and compression molding. During the processing, the starch underwent partial gelatinization, which was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…According to the calculated results, the absorption efficiencies of the composite films all exceeded 99.9%, which clarified that the composite films can efficiently absorb the electromagnetic waves entering their interior. The skin depth, defined as the distance at which the incident electromagnetic wave intensity decays to 1/ e of the initial value, was determined for the composite film using equation : δ = 1 / π f μσ …”
Section: Resultsmentioning
confidence: 99%
“…According to the calculated results, the absorption efficiencies of the composite films all exceeded 99.9%, which clarified that the composite films can efficiently absorb the electromagnetic waves entering their interior. The skin depth, defined as the distance at which the incident electromagnetic wave intensity decays to 1/ e of the initial value, was determined for the composite film using equation : δ = 1 / π f μσ …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, even at low filler content, the composite material exhibits strong electrical conductivity and EMI shielding capability [143][144][145]. Research by numerous investigators has demonstrated that the generation of a segregated structure is advantageous for reducing the percolation threshold of the composite, while synergistic filler interactions enhance the material's shielding ability and mechanical properties [39,40,[146][147][148][149]. The recent studies of segregated-structured electromagnetic shielding materials are summarized in Table 3.…”
Section: Segregated Structurementioning
confidence: 99%